2022
DOI: 10.21037/tcr-22-298
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of LOXL2 knockdown on cellular functions of liver cancer stem cells

et al.

Abstract: Background: Lysyl oxidase-like 2 (LOXL2) plays a role in tumor microenvironment formation and metastasis of hepatocellular carcinoma (HCC), which has a high mortality burden. Liver cancer stem cells (LCSCs) are related with the major malignant phenotypes of HCC. The function of LOXL2 in regulation of LCSCs remains unknown. Methods: CD133 + HepG2 and CD133 + Hep3B cells were sorted by fluorescence-activated cell sorting (FACS) from two human hepatoblastoma cell lines. Spheroid formation, apoptosis, cell cycle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Inhibition of LOXL2 follows the onset of liver brosis and augments collagen degradation [47], which in uences tissue stiffness and resilience [48]. In addition, knockdown of LOXL2 induced apoptosis and cell cycle arrest in liver cancer stem cells [49]. Assessment of the barrier function in addition to immunostaining con rmed the presence of these toxic events in our organoid model.…”
Section: Discussionmentioning
confidence: 71%
“…Inhibition of LOXL2 follows the onset of liver brosis and augments collagen degradation [47], which in uences tissue stiffness and resilience [48]. In addition, knockdown of LOXL2 induced apoptosis and cell cycle arrest in liver cancer stem cells [49]. Assessment of the barrier function in addition to immunostaining con rmed the presence of these toxic events in our organoid model.…”
Section: Discussionmentioning
confidence: 71%
“…Inhibition of LOXL2 follows the onset of liver fibrosis and augments collagen degradation [ 48 ], which influences tissue stiffness and resilience [ 49 ]. In addition, knockdown of LOXL2 induced apoptosis and cell cycle arrest in liver cancer stem cells [ 50 ]. These results indicated that CPZ may lead to barrier disruption of the cholangiocytes, regardless of the cholestatic or non-cholestatic condition.…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of LOXL2-mediated vasculogenic mimicry may enable the development of a new treatment strategy, which could compensate for the side effects of classical antiangiogenic drugs used in HCC treatment. In the study by Li et al, from 2022, the authors demonstrated that the knockdown of LOXL2 effectively inhibited the expression of the anti-apoptosis proteins BIRC3 and MDM2 and induced cell apoptosis and cell cycle arrest in HCC cell lines [135]. However, further research is needed to fully understand the complexities of the LOXL2-mediated apoptosis pathways and their implications in HCC [29,67,[123][124][125][126][127][128][129][130][131][132][133][134][135].…”
Section: Loxl2 and Hypoxia Angiogenesis And Vasculogenic Mimicrymentioning
confidence: 99%